Twitter as a News Source in Data Journalism - Gehrke, Marília; Benetti, Marcia (Brazilian journalism research, 2020)
This paper discusses the use of Twitter as a news source, especially in data journalism. This practice uses public databases as sources for its investigations, but has now started to make use of less conventional sources, such as Twitter, which politicians now use as an official communication channel and thus avoid giving interviews to the press. In this study, we analyze news articles published over a period of a little less than two months by the data journalism team at Vortex Media. Our focus was on political coverage. Twitter may be classified as a reproductive or statistical documentary news sources, depending on the case. We argue that, by using this social networking site as a news source, data journalism could be able to provide new knowledge. Its limitations lie within the working order of the social network itself, which is highly mediated by algorithms and conditioned to spread disinformation. Este artigo discute o uso do Twitter como fonte, em especial no jornalismo guiado por dados. Conhecida por investigar a partir de bancos de dados públicos, esta prática tem acessado fontes menos convencionais, a exemplo da plataforma, à medida que os políticos a tratam como canal oficial de comunicação e evitam conceder entrevistas à imprensa. Neste estudo, analisamos notícias publicadas pela equipe de dados do site jornalístico Vortex Media em pouco menos de dois meses, observando que a cobertura política se destaca nesse contexto. O Twitter pode ser classificado como fonte documental do tipo reprodução ou estatística, dependendo do caso. Defendemos que o jornalismo guiado por dados tem potencial para promover conhecimento inédito a partir do uso desse site de rede social como fonte; suas limitações estão na própria condição da rede, mediada por algoritmos e propícia para o espalhamento de desinformação. Este artículo analiza el uso de Twitter como fuente, especialmente en el periodismo de datos. Conocido por investigar desde bases de datos públicas, esta práctica ha accedido a fuentes menos convencionales, como la plataforma, ya que los políticos la tratan como un canal oficial de comunicación y evitan dar entrevistas a la prensa. En este estudio, analizamos las noticias publicadas por el equipo de datos del sitio periodístico Vortex Media en poco menos de dos meses, señalando que la cobertura política se destaca en este contexto. Twitter puede clasificarse como fuente documental reproductiva o estadística, según el caso. Argumentamos que el periodismo de datos tiene el potencial de promover el conocimiento sin precedentes del uso de este sitio de redes sociales como fuente; sus limitaciones están en la condición de esta red, mediada por algoritmos y propicia para la difusión de la desinformación.